2019
DOI: 10.1016/j.drugalcdep.2018.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Explaining continuity in substance use: The role of criminal justice system involvement over the life course of an urban African American prospective cohort

Abstract: Background: African Americans are disproportionately burdened by substance use consequences and criminal justice system involvement, yet their interrelationship over the life course is not well understood. This study aimed to assess how substance use, crime, and justice system involvement may influence one another from adolescence to midlife. Methods: Data come from a community cohort of urban African Americans first assessed in childhood and followed up into midlife (n = 1242, 606 males, 636 females). We draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Table 2 summarizes the associations between police exposures and health outcomes for the included quantitative studies . Most quantitative studies (13 [81%]) indicated a positive association between police exposures and adverse health for Black youth.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 summarizes the associations between police exposures and health outcomes for the included quantitative studies . Most quantitative studies (13 [81%]) indicated a positive association between police exposures and adverse health for Black youth.…”
Section: Resultsmentioning
confidence: 99%
“…The concern is that these new rules will discourage patients from seeking opioid use treatment in order to avoid persecution and discrimination. Studies have shown that law enforcement interactions increase rather than decrease health risk behaviors such as injection initiation and syringe sharing (Melo et al, 2018 ; Park et al, 2019 ) and that law enforcement involvement in the life of a person who uses drugs is almost unavoidable in the U.S. (Winkelman et al, 2018 ; Green et al, 2019 ). Therefore, a closer look at the way these interactions occur in rural medical settings and for medical purposes is critical to ensure that the rights of people who use drugs are upheld and their health is prioritized.…”
Section: Discussionmentioning
confidence: 99%
“…Among Black adults, substance use disorder may be less associated with willingness to use mental health services because of the linkage between substance use disorder and criminalization of Black adults. Studies show that Black adults are disproportionately criminalized for substance use compared to white adults (46,47).…”
Section: Discussionmentioning
confidence: 99%